Unmasking State Harm: The Border as a Theatrical Space of Gendered Violence - Marmo, Marinella (Violence against women, 2023)
Systemic gendered violence at the borders of the Global North is perpetrated by state actors and their proxies, and yet remains underdiscussed. This article presents numerous cases of such violence to argue that it is not random, does not occur in a vacuum or at the whim of wayward officers. Rather, this gendered state violence is the expression of a patriarchal and hegemonic state that positions the woman at the border as out of place. Deploying performative theories, this article unmasks the masculine agenda enacted at the border to reveal that its violent exhibition of power serves many purposes.